2015
DOI: 10.4028/www.scientific.net/amm.813-814.603
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters of Al-10% Cu Compacts through Powder Metallurgy

Abstract: Powder Metallurgy (P/M) is a manufacturing process in which powders are compacted in a die to attain the final product. P/M has certain unique advantage like controlled porosity, High Strength to weight ratio. Aluminium (Al) is a light weight material, but pure Al does not possess a good strength. To achieve the strength, Copper (Cu) powders are blended at required proportions. Al along with Cu shows good mechanical properties. An attempt is made to optimize the process parameter of Al – 10% Cu powder to attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The remaining 33 articles were screened based on the full article content, where 10 articles were excluded based on the reasons as stated in figure 1. Articles from Scopus database, 7 were excluded [29][30][31][32][33][34][35] and 3 were excluded from ProQuest [36][37][38].…”
Section: Screening Processmentioning
confidence: 99%
“…The remaining 33 articles were screened based on the full article content, where 10 articles were excluded based on the reasons as stated in figure 1. Articles from Scopus database, 7 were excluded [29][30][31][32][33][34][35] and 3 were excluded from ProQuest [36][37][38].…”
Section: Screening Processmentioning
confidence: 99%
“…Zakir Hussain et al [19] examined the powder metallurgy process parameters of diamond-copper composites in terms of compaction pressure, sintering temperature, and holding time and reported that compaction pressure 525 MPa, sintering temperature 900 °C, and holding time 2 h are the most influencing parameters. Pravin et al [20] utilized Taguchi system to optimize the process parameters of Al-10% Cu composites, and the process parameters are compaction load, lubricant, sintering atmosphere, and dwell time and stated that lubricant is a major influencing parameter. Ravichandran and Anandakrishnan [21] examined the PM parameters to obtain higher strength coefficient in aluminium matrix composite via Taguchi method and described that compaction pressure and sintering temperature are major substantial parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Pravin et al fabricated Al-10% copper powder through the powder metallurgy route and evaluated maximum process efficiency via the Taguchi technique. 49 Arifin and Azharuddin investigated the effect of powder-processing parameters on the hardness of fly ash/Al alloy composite through the Taguchi technique. 50 They found that the factors, namely, grain size, holding time, and compacting pressure significantly affected the hardness value of the composite.…”
Section: Introductionmentioning
confidence: 99%